On Devising Unbiased Estimators for the Parameters of the Cobb-Douglas Production Function - Dhrymes, Phoebus J. (Econometrica, 1962)
1. IN MANY empirical investigations the geometric mean of observed factor shares serves as an estimator of the factor exponents in a Cobb-Douglas2 production function. This particular estimator is due to Klein [7, p. 194]. It is here shown that such an estimator is biased. Under certain conditions an alternative estimator is derived which is unbiased, sufficient, efficient, and consistent.